Somatic Experiencing for Posttraumatic Stress Disorder: A Randomized Controlled Outcome Study. Issue 3 (6th June 2017) - Brom, Danny; Stokar, Yaffa; Lawi, Cathy; Nuriel‐Porat, Vered; Ziv, Yuval; Lerner, Karen; Ross, Gina
Abstract : This study presents the first known randomized controlled study evaluating the effectiveness of somatic experiencing (SE), an integrative body‐focused therapy for treating people with posttraumatic stress disorder (PTSD). There were 63 participants meeting DSM‐IV‐TR full criteria for PTSD included. Baseline clinical interviews and self‐report measures were completed by all participants, who were then randomly assigned to study ( n = 33) or waitlist ( n = 30) groups. Study participants began 15 weekly SE sessions, whereas waitlist participants waited the same period, after which the second evaluation was conducted. All participants were evaluated a third time after an additional 15 weeks, during which time the waitlist group received SE therapy. Pretreatment evaluation showed no significant differences between groups. Mixed model linear regression analysis showed significant intervention effects for posttraumatic symptoms severity (Cohen's d = 0.94 to 1.26) and depression (Cohen's d = 0.7 to 1.08) both pre‐post and pre‐follow‐up. This randomized controlled study of SE shows positive results indicating SE may be an effective therapy method for PTSD. Further research is needed to understand who shall benefit most from this treatment modality.